Cardanol e Eugenol Modificados - Uso como antioxidante no controle do processo oxidativo do biodiesel de algodão - Rodrigues Filho, Manoel Gabriel (2010)
Biodiesel is composed by a mixture of different kinds of esters that may have unsaturations in their chains. These unsaturations are susceptible to oxidation processes, especially in the presence of oxygen. The oxidative stability of biodiesel becomes therefore an important quality parameter since the oxidation of the esters may cause some problems when using this fuel. In the search for new technologies to solve this problem, this study used the phenolic substances (cardanol and eugenol) extracted from the liquid cashew not and clove and BHT also phenolic compound, for testing antioxidants in biodiesel cotton. It was made structural changes (hydrogenation) in the compounds cardanol and eugenol to eliminate sites of oxidation (unsaturated) and also increase the initial temperature of decomposition. The results showed that the hydrogenation with an increase in the initial decomposition temperature of 112.70 ° C to 207.80 º C to cardanol and 160 ° C to 175 º C in the case of eugenol. The antioxidant activity of BHT, hydrogenated eugenol and cardonal was detected in combating oxidative bioidesel of cotton during 180 days of storage. We choose cotton biodiesel because oil composition show a high content of unsaturated fatty acids (C16: 1 = 0.20% C18: 1 = 24.30%, C18: 2 = 44.40% and C18: 3 = 5.40%). The test results of the peroxide, iodine, acidity, viscosity and UV-vis spectroscopy showed the following order of activity for the tested compounds: eugenol hydrogenated> cardanol hydrogenated> BHT. This same order of activity was observed when used techniques such as, accelerated oxidation colorimetry exploratory differentiates (PDSC) and PetroOxy. The kinetics of oxidation of the samples doped with the respective compounds reaffirms the same order described previously.